Clinical profiles of adolescents admitted into the intensive care unit at the university college hospital, Ibadan. - Idowu, Olusola Kayode; Fagbohun, Abieyuwa Oghogho; Akindolire, Abimbola Ellen (Student’s Journal of Health Research Africa, 2025)
Background & Objectives The care of the critically ill adolescent in resource-constrained settings such as Nigeria until a few years ago was in the adult ICU (AICU). This care is provided mainly by the adult intensivists with the input from the paediatricians. In the last couple of years, however, paediatric critical care units managed by paediatric intensivists are gradually being established in Nigeria. This study looked at the clinical characteristics of adolescents managed in the adult ICU before the establishment of Paediatric ICU in our centre. This study was carried out to outline the clinical profiles and outcomes of adolescent patients admitted into the adult ICU. Methods This retrospective study was conducted on adolescents admitted over 5 years (2018 to 2022). Results The adolescent population comprised 113(38.6%) of the children and adolescents admitted. The male and female distribution was 65.5% and 34.5% respectively. The mean age was 14.3±2.8 years. The commonest indication for admission was post-surgical excision of intracranial tumours (22.1%). Meningitis with raised intracranial pressure accounted for 17.7% and Haemoglobinopathy with complications (Sepsis, Acute Chest Syndrome, Shock) constituted 10.6%. A third of the adolescent population required ventilation. Amongst ventilated patients, mortality was recorded in 44.1%. Mortality was significantly higher in ventilated than non-ventilated patients (p=0.01). The overall mortality rate was 36.3%. Conclusion The provision of critical care to the adolescent population is important, especially amongst those who require ventilatory support as they are at high risk of mortality.